Evaluation of the efficacy of ethanol extract from black shallot (Allium ascalonicum) in reducing oxidative stress and modulating immune response in a paracetamol-induced nephrotoxicity mouse model. - Nhung, T. T. P.; Quoc, L. P. T. (International Journal of Agricultural Technology, 2025)
The protective effects of ethanol extract from black shallot (ESBA) and N-acetylcysteine (NAC) against paracetamol (PARA)-induced nephrotoxicity in mice were investigated. Notable changes in body weight, relative kidney weight, and kidney structure were observed, with the normal group exhibiting the highest body weight (40.34 ± 0.42 g) (p < 0.05) and the lowest relative kidney weight (28.61 ± 0.23%) (p < 0.05). In contrast, the PARA group showed reduced body weight (27.66 ± 0.46 g) (p < 0.05) and increased relative kidney weight (68.99 ± 0.82%) (p < 0.05). Treatment with NAC and ESBA improved these parameters, with the PARA+NAC and PARA+ESBA400 groups approaching normal values. Furthermore, malondialdehyde (MDA) and hydrogen peroxide (H₂O₂) levels were significantly elevated in the PARA group (p < 0.05), indicating oxidative stress, while NAC and ESBA supplementation effectively reduced these levels across all tissues (p<0.05). Analysis of glutathione (GSH) and total antioxidant capacity (TAC) revealed higher levels in the normal group compared to the PARA group (p < 0.05), with NAC and ESBA restoring GSH and TAC levels (p < 0.05). Antioxidant enzyme activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were also significantly improved with treatment (p < 0.05). Additionally, immunomodulatory effects were observed, as evidenced by changes in white blood cell count, nitroblue tetrazolium positivity, and total immunoglobulin levels (p < 0.05). ESBA treatment notably restored immune function by decreasing inflammation markers and enhancing phagocytic activity (p < 0.05). These findings suggested that NAC and ESBA exhibit protective effects against PARA-induced nephrotoxicity through antioxidant and immunomodulatory mechanisms.